Comparison of vascular cell adhesion molecule 1 (VCAM-1) during pregnancy, after placental detachment and during puerperium between normal and pregnancy with COVID-19 - Pasaribu, Hotma P.; Lumbanraja, Sarma N.; Varenni, Wijitha; Enitan, Seyi S. (Narra J, 2023)
Pregnant women have a number of physiological changes that lower the immune responses to avoid embryonic rejection, which increases the risk of problems after contracting coronavirus disease 2019 (COVID-19). Multiple inflammatory cytokines are dysregulated in this process and expressed inappropriately during systemic inflammatory responses associated with COVID-19. The aim of the study was to compare the levels of vascular cell adhesion molecule 1 (VCAM-1), a marker of endothelial damage in pregnancies with and without COVID-19. A cohort prospective study was conducted at H. Adam Malik General Hospital and the Universitas Sumatera Utara Hospital, Indonesia. Pregnant women without COVID-19 and pregnant women with moderate and severe degrees of COVID-19 were recruited. The level of VCAM-1 was measured at three different time points (during pregnancy, within an hour of placental detachment, and 24 hours postpartum). The ANOVA and Student t-test were used to compare the VCAM-1 levels among different time points and between groups, respectively. The mean VCAM-1 levels at the hospital admission, one hour of placental detachment and 24 hours postpartum in non-COVID-19 and COVID-19 pregnancies were 591.29 vs 1176.27 pg/mL; 558.2 vs 1136.2 pg/mL; and 508.59 vs 985.2 pg/mL, respectively. There was a significant different in VCAM-1 levels in normal pregnancy at the time of hospital admission, one hour after detachment of the placenta and 24 hours postpartum (p=0.04). The mean VCAM-1 levels in pregnant women with COVID-19 also had significant differences between three time points (p=0.033). The levels of VCAM-1 were statically higher among pregnancy in the COVID-19 group compared to the non-COVID-19 group during hospital admission (p=0.023), one hour after placenta detachment (p=0.040) and 24 hours postpartum (p=0.043).The results suggested the usefulness of identifying the VCAM-1 level as a marker of endothelial dysfunction in pregnancy with COVID-19.